Difficulties in Histological diagnosis and treatment of Hirschprung’s disease - More-Flores, Mario Marcelino (2020)
Traditionally Hirschsprung´s disease has been diagnosed and treated under the paradigm of the absence of submucosal and myenteric nerve plexus in a localized area of the colon. Surgical treatment consists of resection of the aganglionic area and anastomosis of the anal level of the ganglionic region of  the colon. The review of the long-term results of the surgery, with the various surgical techniques existing up to now show complications related to incontinence and constipation in about 50 % of the cases. Many surgeons think that this disease is still unknown and even incurable. With the advancement in the field of research in molecular biology in the been discovered that addition to the absence of the nerve plexuses, and the Cajal cells in the aganglionic segment, failure in the secretion of mediators called purinergic, such as the ATP and its receptors, as well nitrate substance such as nitric oxide, which intervene in the relaxations of the intestinal muscle. On the other hand, research in the field of genetics has allowed us to know the role of pro-oncogenes mutations such as RET and others, in the genesis of Hirschsprung´s disease. In this paper. A review of the above-mentioned concepts is made and the difficulties in the histological diagnosis of the disease are discussed and a rational and intelligent approach is proposed, found in the reviewed literature.